Diagnostic pitfall in fine needle aspiration cytology of pilomatrixoma with unusual clinical presentation - Alzalla, Omar; Mat Zin, Anani Aila; Mahayidin, Hasni; Bakrin, Ikmal Hisyam (Universiti Putra Malaysia, 2021)
Pilomatrixoma (PMX) is a benign skin adnexal tumour with matrical differentiation. It frequently presents as a painless and slow growing solitary skin nodule primarily at the head, face and neck regions. Although there is increasing understanding on the clinical presentations and morphological features of PMX, difficulties are still expected in establishing the clinical and cytological diagnosis. We report a young girl who presented with a painless post-auricular swelling for one year with sudden increased in size. Computed Tomography (CT) scan and fine needle aspiration cytology (FNAC) findings were suggestive of a malignancy. Diagnosis of PMX was established and confirmed by tissue histopathological examination. The purpose of this study is to demonstrate the diagnostic pitfall of PMX in FNAC specimens, especially in patients with unusual clinical presentations.